Pengaruh Tax Morale Dan Tax Awareness Terhadap Kepatuhan Wajib Pajak Orang Pribadi Non-Karyawan Yang Terdaftar Di Kota Balikpapan - Noor Maulida, Sheilla; Abadan Syakura, Muhammad (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
This study aims to determine the influence of tax morale and tax awareness on the compliance of non-employee individual taxpayers registered in the West and East Balikpapan Primary Tax Office (KPP Pratama Balikpapan Barat and Timur). This research is quantitative in nature and employs primary data. The sample size used in this study consists of 100 respondents of non-employee individual taxpayers registered in the West and East Balikpapan Primary Tax Office (KPP Pratama Balikpapan Barat and Timur). The data analysis tool used in this research is Partial Least Square (PLS) ver 4.0. The results of this study indicate that tax morale has a positive and significant influence on the compliance of non-employee individual taxpayers, and tax awareness influences the compliance of non-employee individual taxpayers.